2017
DOI: 10.3390/cryst8010010
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Influence of A1, 5A, and W51W57 Mutations on the Conductivity of the Geobacter sulfurreducens Pili

Abstract: Abstract:The metallic-like conductivity of the Geobacter sulfurreducens pilus and higher conductivity of its mutants reflected that biological synthesis can be utilized to improve the properties of electrically conductive pili. However, the structural basis for diverse conductivities of nanowires remains uncertain. Here, the impacts of point mutations on the flexibility and stability of pilins were investigated based on molecular dynamics simulations. Structures of the G. sulfurreducens pilus and its mutants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…sulfurreducens. The pilin-based polymer, called a pilus, was hypothesized to transport electrons through a continuous chain of stacked aromatic residues (Figure , top left ) by either multistep charge hopping or bandlike charge transport. However, a recently reported cryogenic electron microscopy (CryoEM) structure differed markedly from the proposed model (Figure , top middle vs top left ) and had a conductivity 10 4 times smaller than what was previously attributed to the pilus . The electrically conductive or e -pili have been suggested to not exist as such, , being instead the misidentified filamentous outer-membrane cytochrome type S (OmcS) (Figure , top right ) …”
Section: Introductionmentioning
confidence: 99%
“…sulfurreducens. The pilin-based polymer, called a pilus, was hypothesized to transport electrons through a continuous chain of stacked aromatic residues (Figure , top left ) by either multistep charge hopping or bandlike charge transport. However, a recently reported cryogenic electron microscopy (CryoEM) structure differed markedly from the proposed model (Figure , top middle vs top left ) and had a conductivity 10 4 times smaller than what was previously attributed to the pilus . The electrically conductive or e -pili have been suggested to not exist as such, , being instead the misidentified filamentous outer-membrane cytochrome type S (OmcS) (Figure , top right ) …”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, a previous study has shown that the genetic substitution of an alanine for each of the three tyrosine (+27, +32, and +57) and two of the phenylalanine (+24 and +51) in PilA resulted in an assembled pilus with poor conductivity [15]. Genetic substitution of an alanine for the phenylalanine (+1) in PilA, the pilus subunit, resulted in assembled pili likely with poor conductivity, further indicating the importance of F1 aromatic amino acids in electron transport [43]. These results suggest that these genetic substitutions resulted in different GS pilus conformations, which probably resulted in various electron transfer rates of G. sulfurreducens pilus.…”
Section: Resultsmentioning
confidence: 99%
“…These observations have been rationalized in terms of the metallic-like pilus (MLP) hypothesis, with the homology-modeled prediction of a seamlessly stacked array of aromatic residues (Figure 1A) (Malvankar et al, 2015;Xiao et al, 2016;Shu et al, 2017Shu et al, , 2019Shu et al, , 2020. Inspired by this picture, experiments on modified or de novo designed proteins lacking redox active cofactors have demonstrated, in some cases, electrical conductivities that are surprisingly high and due to mechanisms under active investigation (Creasey et al, 2015;Kalyoncu et al, 2017;Ing et al, 2018b;Shapiro et al, 2022;Krishnan et al, 2023).…”
Section: Introductionmentioning
confidence: 92%